Use of metaphylactic protocols based on the risk to develop bovine respiratory diseases in feedlot cattle - Magalhães,Layane Queiroz (2017)
ABSTRACT: Bovine respiratory diseases (BRD) affect production rates negatively because it compromise health and well-being of the affected animal. The hypothesis of this study was that the use of metaphylactic protocols based on the risk to develop BRD would reduce morbidity and pulmonary lesions. For this purpose, the aims of this study were to evaluate the effect of two metaphylactic protocols on the morbidity of feedlot cattle with a known sanitary history, occurrence of pulmonary lesions at slaughter, and the possible participation of Mannheimia haemolytica, Histophilus somni, Bovine alphaherpesvirus 1 (BoHV-1) and bovine respiratory syncytial virus (BRSV) in the development of BRD. An experimental study was designed in which 3,094 adult, male, cattle, were grouped according to the risk to develop BRD: a) group without metaphylaxis (n=2,104), low-risk animals; b) metaphylaxis group with oxytetracycline (n=789), moderate-risk animals; c) metaphylaxis group with tildipirosin (n=201), high-risk animals. All cattle were immunized against pathogens associated with BRD (BoHV-1, BVDV, BRSV, PI3). The morbidity for BRD was 8.2% (253/3,094); cattle within the moderate-risk group for BRD had the lowest frequency (6.1%), followed by high-risk animals with tildipirosin metaphylaxis (6.5%) and low-risk without metaphylaxis (9.1%) (P=0.019). At the abattoir, 1.2% of lungs with lesions were found. There was a difference (P=0.036) in the frequency of pulmonary lesions between healthy animals (1.1%) and those diagnosed with BRD (2.8%). Two agents associated with BRD were identified by PCR assays in the lungs (n=37) of cattle: M. haemolytica (16.2%) and H. somni (5.4%). In addition, concomitant infections involving these pathogens were identified in the lungs of two steers. These results demonstrate that the use of metaphylactic protocols, based on the risk to develop BRD, reduces morbidity and pulmonary lesions in affected cattle. Furthermore, pulmonary lesions were more frequent in animals with a history of BRD.